2011
DOI: 10.1002/bdrc.20219
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac developmental toxicity

Abstract: Congenital heart disease is a highly prevalent problem with mostly unknown origins. Many cases of CHD likely involve an environmental exposure coupled with genetic susceptibility, but practical and ethical considerations make nongenetic causes of CHD difficult to assess in humans. The development of the heart is highly conserved across all vertebrate species, making animal models an excellent option for screening potential cardiac teratogens. This review will discuss exposures known to cause cardiac defects, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…There have been some data supporting an increased risk of cardiac malformations with an even higher risk if the exposure occurred during the firsttrimester. This includes ventricular outflow defects and atrial/ventricular septal defects 6,7 (Figures 2-4). Fluoxetine (Prozac) and sertraline (Zoloft) are other SSRIs that may be associated with cardiac malformations.…”
Section: Antidepressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some data supporting an increased risk of cardiac malformations with an even higher risk if the exposure occurred during the firsttrimester. This includes ventricular outflow defects and atrial/ventricular septal defects 6,7 (Figures 2-4). Fluoxetine (Prozac) and sertraline (Zoloft) are other SSRIs that may be associated with cardiac malformations.…”
Section: Antidepressantsmentioning
confidence: 99%
“…In small studies, it was found to be associated with left outflow tract defects. 7 Importantly, data for all antidepressants are conflicting. There has not been a single antidepressant that has been definitively associated with CHD.…”
Section: Antidepressantsmentioning
confidence: 99%
“…Congenital heart defects arise when genetic and/or environmental perturbations undermine normal cardiac development (reviewed by Bruneau, 2008;Epstein, 2010;Mahler and Butcher, 2011;Srivastava and Olson, 2000). As a class, they cause significant mortality during all stages of human life (Roger et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…All things considered, however, at this time it appears safe to say that the minimum of 80% given by van Mil et al (2010) is useful as a guideline for estimating the role of gene-environment interactions as the cause of CHD. The extraordinary complexity of gene-gene and gene-environment interactions in development is just beginning to be appreciated in the early 21 st century (Finnell et al, 2004(Finnell et al, , 2008Zhu et al, 2009;van Mil et al, 2010;Hobbs et al, 2011;Mahler and Butcher, 2011).…”
Section: Introductionmentioning
confidence: 99%